2017
DOI: 10.1111/age.12555
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the International Society for Animal Genetics recommended parentage and identification panel for the domestic pigeon (Columba livia domestica)

Abstract: In this study, the International Society for Animal Genetics (ISAG) recommended panel for the identification of the domestic pigeon (Columba livia domestica) is characterized based on commonly used statistical parameters. The marker panel is based on 16 short tandem repeat (STR) loci (PIGN15, PIGN10, PIGN57, PIGN26, CliμD16, CliμD19, PIGN12, CliμD17, CliμT17, PIGN04, CliμD01, CliμD11, CliμD35, CliμT02, CliμT13, CliμT43). The alleles of the 16 loci consist of a mixture of tri-, tetra-, penta- and hexameric repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Due to the difficulty in determining the sex of an adult bird, a sexing marker was added to the panel as an extra quality control. The results demonstrated the applicability of the panel in parentage verification and identity control for the domestic pigeon in both routine laboratory settings and casework …”
Section: Nonhuman Dnamentioning
confidence: 87%
See 1 more Smart Citation
“…Due to the difficulty in determining the sex of an adult bird, a sexing marker was added to the panel as an extra quality control. The results demonstrated the applicability of the panel in parentage verification and identity control for the domestic pigeon in both routine laboratory settings and casework …”
Section: Nonhuman Dnamentioning
confidence: 87%
“…The results demonstrated the applicability of the panel in parentage verification and identity control for the domestic pigeon in both routine laboratory settings and casework. 159 Investigations of threatened animals are important, as there can be a link between animal abuse and human violence. For this reason, DNA techniques have been often used to assist in animal cruelty investigations.…”
Section: ■ Nonhuman Dnamentioning
confidence: 99%
“…The current microsatellite panel recommended by ISAG for pigeons was proposed by the Committee of the Society, which is now called ‘Applied Genetics and Genomics in other Species of Economic Interest’ and has been successfully used by other standardized laboratories that also provide services in the field of personal identification and parentage testing. VHL Genetics undertakes pigeon population studies with the use of these markers [ 43 ]. The authors in this study, based on the statistical analysis, demonstrated the usefulness of this panel, paying attention to parameters such as combined exclusion probability-first parent, combined exclusion probability-second parent, and combined exclusion probability-parent pair, where they obtained the values of 99.86%, 99.99%, and 99.99%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2009), domesticated cats (Lipinski et al . 2007) and even species of lesser economic importance like pigeons (de Groot & Van Haeringen 2017). They result in high rates of individual identification and parental exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Panels were developed based on STRs owing to their high discriminatory characteristics, which result in a high rate of parental or identification exclusion. Probability of exclusion (PE) values of greater than 0.99 in many species can be obtained by combining approximately 15 polymorphic STR markers in one multiplex PCR (de Groot & Van Haeringen 2017). A transition to SNPs for parentage verification and identification for production animals has attracted much interest (Heaton et al .…”
Section: Introductionmentioning
confidence: 99%